Credibility Enacted: Understanding the Meaning of Credible Political Leadership in the Dutch Parliamentary Election Campaign of 2010. Issue 3 (3rd July 2018) - Van Zuydam, Sabine; Hendriks, Frank
Abstract : In times of perception politics, the credibility of electoral candidates is a crucial asset in political marketing. This raises the question to which political leaders citizens attribute credibility and how political credibility is gained and lost through media performance. We analyze and compare two contrasting cases during the Dutch parliamentary election campaign of 2010. Whereas in this campaign Mark Rutte—leader of the liberal party VVD—gained credibility, the credibility of Job Cohen—at the time, leader of the social-democratic PvdA—waned substantially. To understand this we extend the source credibility approach with a dramaturgical approach, and as such we shed light on what happens in the dynamic, interactive process between leaders and audiences in which credibility is constructed.